Biodegradation of Mycotoxins: Tales from Known and Unexplored Worlds - Vanhoutte, Ilse; Audenaert, Kris; De Gelder, Leen (Frontiers in Microbiology, 2016)
Exposure to mycotoxins, secondary metabolites produced by fungi, may infer serious risks for animal and human health and lead to economic losses. Several approaches to reduce these mycotoxins have been investigated such as chemical removal, physical binding or microbial degradation. This review focuses on the microbial degradation or transformation of mycotoxins, with specific attention to the actual detoxification mechanisms of the mother compound. Furthermore, based on the similarities in chemical structure between groups of mycotoxins and environmentally recalcitrant compounds, known biodegradation pathways and degrading organisms which hold promise for the degradation of mycotoxins are presented.